2008
DOI: 10.17660/actahortic.2008.801.3
|View full text |Cite
|
Sign up to set email alerts
|

Innovation in Greenhouse Engineering

Abstract: Innovations in greenhouse engineering are technical developments which help evolve the state-of-the-art in CEA (Controlled Environment Agriculture). They occur in response to the operational demands on the system, and to strategic changes in expectations of the production system. Influential operational factors include availability of labor, cost for energy, logistics of transport, etc. Influential strategic factors result from broader, regional issues such as environmental impact, product safety and consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The Naples event of the Greensys 2007 symposium (Giacomelli, 2007) demonstrated that room for improvement in greenhouse cropping is evident. In Naples, the main focus was on a famous closed greenhouse prototype named Watergy Regarding innovation in greenhouse engineering, Giacomelli (2007) points out in his address that: (1) greenhouse components and designs directly impact on crop growth; (2) correctly assessing the importance of crop-greenhouse interactions is needed; (3) real-time measuring of a maximum number of parameters is necessary; and (4) other than the Watergy project, engineers have to find the ways and means to substantially reduce energy and water use and to ensure that an acceptable return on investment can be achieved when high enough yields are produced.…”
Section: New Generation Greenhousesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Naples event of the Greensys 2007 symposium (Giacomelli, 2007) demonstrated that room for improvement in greenhouse cropping is evident. In Naples, the main focus was on a famous closed greenhouse prototype named Watergy Regarding innovation in greenhouse engineering, Giacomelli (2007) points out in his address that: (1) greenhouse components and designs directly impact on crop growth; (2) correctly assessing the importance of crop-greenhouse interactions is needed; (3) real-time measuring of a maximum number of parameters is necessary; and (4) other than the Watergy project, engineers have to find the ways and means to substantially reduce energy and water use and to ensure that an acceptable return on investment can be achieved when high enough yields are produced.…”
Section: New Generation Greenhousesmentioning
confidence: 99%
“…In Naples, the main focus was on a famous closed greenhouse prototype named Watergy Regarding innovation in greenhouse engineering, Giacomelli (2007) points out in his address that: (1) greenhouse components and designs directly impact on crop growth; (2) correctly assessing the importance of crop-greenhouse interactions is needed; (3) real-time measuring of a maximum number of parameters is necessary; and (4) other than the Watergy project, engineers have to find the ways and means to substantially reduce energy and water use and to ensure that an acceptable return on investment can be achieved when high enough yields are produced. In the opinion of Prof. Stefania De Pascale, convener of Greensys 2007, a greenhouse system is in some respect already an energy-saving system compared to open field agriculture and is an excellent environment to achieve an optimal balance between an efficient environmental control and an efficient plant use of the available resources (Giacomelli, 2007).…”
Section: New Generation Greenhousesmentioning
confidence: 99%
“…An agricultural greenhouse (GH) is an enclosed transparent house used to protect crops from critical ambient climate conditions and pests, and provide the opportunity to adjust the indoor microclimate suitable for crop growth and production, both in terms of quantity and quality [6]. GH enables year-round crop production and improves the yield and quality of crops through control of the physical environmental factors such as light, water, temperature, relative humidity, CO2 concentration, and ventilation [7]. GH technology can guarantee the sustainable and secure food production by increasing the production yield up to ten times more [1], and decreasing the 11.8 m 3 /d per capita water requirements by 80 % compared to conventional cultivation [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, these averaged climatic conditions and 2 Mathematical Problems in Engineering strategies are the result of a dynamic interaction between the greenhouse structures and the varying daily values of outdoor temperature, solar irradiance, relative humidity, and wind velocity. In spite of the overall good performance shown above, it is possible that in a relevant number of hours over the year, active measures are required to maintain crop growth and increase greenhouse productivity [7][8][9]. In addition to this, the passive and eventually active climate control strategies must address both demands: heating and cooling, introducing an added complexity factor to the system's selection and operation [10].…”
Section: Introductionmentioning
confidence: 99%